A dickson-type adder/subtractor dc-dc converter realizing step-up/step-down conversion - Eguchi, Kei; Julsereewong, Prasit; Julsereewong, Amphawan; Fujimoto, Kuniaki; Sasaki, Hirofumi (My University, 2013)
In this paper, a Dickson-type adder/subtractor DC-DC converter realizing step-up/step-down conversion is proposed. Although the conventional Dickson converter cannot achieve step-up/step-down conversion, the proposed converter can provide not only the stepped-up voltage but also the stepped-down voltage by combining the battery energy and the clean energy. Moreover, the proposed converter can achieve many con-version ratios by utilizing hybrid inputs. Therefore, by choosing the optimal combination of conversion ratio, the proposed converter can alleviate the energy loss caused by the output regulation. To evaluate circuit properties, theoretical analyses, simulations and experiments were performed concerning a simple example of the proposed converter. Cir-cuit simulations and experiments showed the following results: (1) The circuit design is appropriate, because the step-up/step-down conversion was confirmed by the experimen-tal circuit. (2) The number of conversion ratios of the proposed converter is three times as large as that of the conventional three-stage ring-type converter. (3) The proposed converter can reduce more than 25% hardware cost than the conventional converter. (4) The derived theoretical formulas are useful to estimate the characteristics of the proposed converter, because the theoretical result corresponded well with the simulated result. © 2013 ICIC International.
Keywords: Charge pump; Clean energy; Hybrid inputs; Step-up/step-down converters; Switch-ed capacitor circuits; Switching converters